Convincing Yourself to Care About Others: An Intervention for Enhancing Benevolence Values. Issue 1 (8th April 2013) - Arieli, Sharon; Grant, Adam M.; Sagiv, Lilach
Abstract To study value change, this research presents an intervention with multiple exercises designed to instigate change through both effortful and automatic routes. Aiming to increase the importance attributed to benevolence values, which reflect the motivation to help and care for others, the intervention combines three mechanisms for value change (self‐persuasion, consistency‐maintenance, and priming). In three experiments, 142 undergraduates (67% male, ages 19–26) participated in an intervention emphasizing the importance of either helping others (benevolence condition) or recognizing flexibility in personality (control condition). We measured the importance of benevolence values before and after the task. In Experiment 1, the intervention increased U.S. participants' benevolence values. In Experiment 2, we replicated these effects in a different culture (Israel) and also showed that by enhancing benevolence values, the intervention increased participants' willingness to volunteer to help others. Experiment 3 showed that the increases in the importance of benevolence values lasted at least 4 weeks. Our results provide evidence that value change does not require fictitious feedback or information about social norms, but can occur through a 30‐min intervention that evokes both effortful and automatic processes.